ANALISIS STATISTIK PARAMETRIK PERBEDAAN SIGNIFIKAN DALAM KENAIKAN HARGA AYAM DI PASAR SEJAHTERA KABUPATEN BEKASI (Jurnal Ekonomi dan Bisnis, 2025)
This study aims to help provide answers whether the increase in chicken prices at Pak Selamet's umkm in the prosperous market in the last three years, the difference in price increases is still considered significant or not. This research applies the one-way ANOVA test to ensure statistical quality and applies a quantitative approach through descriptive data collection using observation and interview techniques. Based on the findings of the ANOVA test which obtained the results of the P-Value
Keywords: Price Increase; Normality Test; Homogeneity Test; One Way Anova Test; Tukey Test